Multivitamin supplement use and risk of invasive breast cancer - Meulepas, Johanna M. (2009)
BACKGROUND: Multivitamin supplements are used by nearly half of middle aged women in the United States. Despite this high prevalence of multivitamin use, little is known about the effects of multivitamins on health outcomes, including cancer risk. OBJECTIVE: Our main objective was to determine the association between multivitamin use and the risk of breast cancer in women. DESIGN: We conducted a population-based case-control study among 2,968 incident breast cancer cases (ages 20–69 years) diagnosed between 2004–2007, and 2,982 control women from Wisconsin, U.S.A. All participants completed a structured telephone interview which ascertained supplement use prior to diagnosis, demographics, and risk factor information. Odds ratios (ORs) and 95% confidence intervals were calculated using multivariable logistic regression. RESULTS: Compared to never users of multivitamins, the ORs for breast cancer were 1.02 (95%CI: 0.87–1.19) for current users and 0.99 (95%CI: 0.74–1.33) for former users. Further, neither duration of use (for ≥ 10 years, OR= 1.13, 95%CI: 0.93–1.38, ptrend: 0.25) nor frequency (>7 times/week, OR= 1.00, 95%CI: 0.77–1.28, ptrend: 0.97) was related to risk in current users. Stratification by menopausal status, family history of breast cancer, age, alcohol, tumour staging and post-menopausal hormone use did not significantly modify the association between multivitamin use and breast cancer. CONCLUSION: This study found no association between multivitamin supplement use and breast cancer risk in women.